PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA PEMBELAJARAN BAHASA INDONESIA DI KELAS IV SDN 139/I SUNGAI BULUH - Juliska, Landia Octa; Nurjanah, Fitrima; Andriani, Oktavia; Fadzillah, Rhodhiathi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to increase students' conceptual understanding by applying the problem based learning model to Indonesian language learning in class IV at SD N 139/I Sungai Buluh. The research method used is Classroom Action Research (PTK), referring to the Kemmis and Mc's model. Taggart consists of four steps: 1) Plan, 2) Observe, 3) Implement, and 4) Reflect. The subjects of this research were 21 grade IV students at SD N 4 139/I Sungai Buluh, consisting of 10 boys and 11 girls. Data collection techniques use test and non-test techniques. Test techniques are carried out through learning assessment tests given at the end of the cycle, while non-test techniques used include: 1) observation or observations; Includes teacher skills observation sheet and concept understanding observation sheet. 2) interviews, especially structured interviews, and 3) documentation. The data inspection technique used is expert judgment content validity. The data analysis technique was carried out descriptively comparatively. The research results showed that the use of the problem based learning model was able to increase students' conceptual understanding in the knowledge aspect of Cycle I, with an average score of 72.428. In cycle II the average value rose again to 75.285. The average teacher competency score in Cycle I was 67% and Cycle II was 78%. Based on the data above, it can be concluded that the use of the problem-based learning model improves students' ability to understand concepts in Chapter V